Hubungan Pengetahuan Gizi, Status Sosial Ekonomi Keluarga, Konsumsi Sugar Sweetened Beverages dengan Status Gizi Lebih pada Remaja di SMPN 9 Kota Jambi - Sari, Diana; Chandra, Filius; Gustra Jeki, Andicha (3031-8572, 2024)
The prevalence of overweight among adolescents is a significant health issue that can be influenced by various factors, including nutrition knowledge, family socioeconomic status, and consumption of sugar-sweetened beverages (SSBs). This study was conducted at JHS 9 in Jambi City to explore the relationships between these factors and overweight status among adolescents. The aim of this research is to analyze the relationship between nutrition knowledge, family socioeconomic status, and SSB consumption with overweight status among adolescents at JHS 9 in Jambi City. The study used a correlational analytical design with a sample of 39 adolescents. Data were collected through questionnaires to assess nutrition knowledge, socioeconomic status, and SSB consumption, as well as anthropometric measurements to evaluate overweight status. The majority of respondents had inadequate nutrition knowledge (76.9%), low socioeconomic status (61.5%), and high SSB consumption (87.2%). Data analysis revealed no significant relationships between nutrition knowledge, socioeconomic status, and SSB consumption with overweight status among the adolescents at the study site. These findings suggest that nutrition knowledge, socioeconomic status, and SSB consumption are not significantly related to overweight status among adolescents at JHS 9 Jambi City. This indicates the need for further exploration of other factors that might contribute to overweight status, as well as a more comprehensive approach in future research